Modeling the system of beliefs that influence driving under the influence of cannabis (DUIC). (March 2021) - Scott, Brandon; Ward, Nicholas; Otto, Jay; Finley, Kari
Highlights: Reported DUIC behavior (frequency and recency) was predicted by willingness that influenced intention. Willingness and intention were directly influenced by control beliefs, attitudes, norms, and attitudes (prototype image). Intention had a stronger influence on DUIC than willingness alone. The predictive components were influenced by underlying behavioral, normative, and control beliefs. Thus, strategies that can change these beliefs may also reduce DUIC. Abstract: Cannabis use is increasing in the U.S. Driving under the influence of cannabis (DUIC) may be increasing as well potentially resulting in fatal and serious injury crashes. The purpose of this article is to explore the belief system associated with driving under the influence of cannabis (DUIC) using structural equation modeling (SEM). A sample (n = 2, 084) of surveys collected from adults in the U.S. was analyzed using SEM to reveal the latent structure of the belief system associated with DUIC. The results of this analysis indicated that reported DUIC behavior (frequency and recency) was predicted by willingness that influenced intention. Willingness and intention were directly influenced by control beliefs, attitudes, norms, and attitudes (prototype image) toward people who never DUIC. Intention was also influenced by attitudes toward people who do DUIC. Intention had a stronger influence on DUIC than willingness alone. These components were influenced by underlying behavioral, normative, and control beliefs. Thus, strategies that can change these beliefs may also reduce DUIC.